Management strategies to counteract the barriers to social innovation in public health companies - Ramírez Molina, Ramineth Joselin; González Pertúz, Blanca Liliana; Ramírez Molina, Reynier Israel; Lay Raby, Nelson David (Revista Venezolana de Gerencia, 2026)
Social innovation drives social transformations through sustainable and novel solutions, providing the necessary tools to address inequality and injustice while generating significant positive societal impacts. This research is grounded in the theories of Jareh (2025), OECD/Eurostat (2018), and Zaar (2022), among others. The study aimed to determine management strategies to counteract barriers to social innovation within public health enterprises. Methodologically, the research employs a quantitative approach, characterized as descriptive with a non-experimental, cross-sectional, and field-based design. The sample consisted of thirty (30) board members from public health companies in Magdalena, Colombia. The findings reveal a mean of 3.58 with a standard deviation of 0.67, placing social innovation barriers in the “moderate” category according to the interpretation scale (range: 3.40–4.19). Notably, the “social challenges” indicator received the highest score at 3.67. The study concludes that the presence of these barriers highlights the urgent need to mitigate obstacles through participatory, adaptive, and inclusive management strategies. Such multidimensional and intersectoral responses are essential to foster sustainable transformations and co-create accessible, resilient health systems capable of navigating the complex dynamics of the 21st century.